Brand dan Public Relation: Sebuah Kajian Konseptual dalam Konteks Indonesia - Dewi Warda Wibowo; Avizatuz Zahro; Pratiwi Yuni Rahayu; Miftahul Huda (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
This research aims to analyze the conceptual relationship between brands and public relations (PR) in the context of business and socio-cultural dynamics in Indonesia. Through a literature study method with a qualitative approach, this research explores the role of PR in building brand identity, managing reputation, and facing challenges in the digital era. The study focuses on three main aspects: (1) the development of the brand concept in Indonesia which is not only a visual identity, but also a representation of values ​​and emotional relationships with consumers; (2) definition and function of PR as a strategic communication tool to create a positive image; and (3) integration of brand and PR in a communication strategy that is adaptive to local characteristics. Initial findings show that brand-PR synergy in Indonesia requires a participatory approach, message consistency, and the use of digital media, emphasizing cultural values ​​such as family and religiosity.